Customization of open source applications to support a multi-institution digital repository using DSpace - Benchouaf, Youssef, author; Hamp, Daniel, author; Shelstad, Mark, author; D-Lib Magazine, publisher (Colorado State University. Libraries, 2016)
Colorado State University, along with seven other academic institutions and a university press, migrated out of DigiTool to DSpace in the fall of 2015. This article will analyze the customizations made to the application, including assigning multiple handles; automating ingest of electronic theses and dissertations; mapping of multiple schema (METS, MODS, MARC) to Dublin Core; modifying the Simple Archive Format for ingest; Kaltura for ingesting bulk video submissions; and harvesting the OAI feed for CSU's web site, discovery layer, and other repositories. A number of processes for ingest have been automated or made available to non-system staff, resulting in significant cost and time savings.